Cholesterol-Lowering Effects of Asperidine B, a Pyrrolidine Derivative from the Soil-Derived Fungus Aspergillus sclerotiorum PSU-RSPG178: A Potential Cholesterol Absorption Inhibitor - Atcharaporn Ontawong; Acharaporn Duangjai; Yaowapa Sukpondma; Kwanruthai Tadpetch; Chatchai Muanprasat; Vatcharin Rukachaisirikul; Jakkapong Inchai; Chutima S. Vaddhanaphuti (MDPI AG, 2022)
Isolated secondary metabolites asperidine B (preussin) and asperidine C, produced by the soil-derived fungus Aspergillus sclerotiorum PSU-RSPG178, were found to exhibit inhibitory effects against 3-hydroxy-3-methyl-glutaryl-coenzyme A reductase and oxidative stress in an in vitro assay. Whether or not the known pyrrolidine asperidine B and the recently isolated piperidine asperidine C have lipid-lowering effects remains unknown. Thus, this study aimed to investigate the hypocholesterolemic effects of asperidines B and C and identify the mechanisms involved in using in vitro, ex vivo, and in vivo models. The results show that both compounds interfered with cholesterol micelle formation by increasing bile acid binding capacity, similar to the action of the bile acid sequestrant drug cholestyramine. However, only asperidine B, but not asperidine C, was found to inhibit cholesterol uptake in Caco-2 cells by up-regulating LXRα without changing cholesterol transporter NPC1L1 protein expression. Likewise, reduced cholesterol absorption via asperidine-B-mediated activation of LXRα was also observed in isolated rat jejunal loops. Asperidine B consistently decreases plasma cholesterol absorption, similar to the effect of ezetimibe in rats. Therefore, asperidine B, the pyrrolidine derivative, has therapeutic potential to be developed into a type of cholesterol absorption inhibitor for the treatment of hypercholesterolemia.